Waste seeds of Mangifera indica, Artocarpus heterophyllus, and Schizizium commune as biochar for heavy metal removal from simulated wastewater - Giri, Deen Dayal; Jha, Jay Mant; Srivastava, Neha; Shah, Maulin; H. Almalki, Atiah; F Alkhanani, Mustfa; Pal, Dan Bahadur (Springer Science and Business Media Deutschland GmbH, 2023)
The threat of arsenic contamination in water is a challenging issue worldwide. Millions of people utilize untreated groundwater having high levels of arsenic in developing countries. Design Expert 6.0.8 has been used to design experiments and carried out statistical analysis for optimization of different parameters. It is of prime importance to develop cheap environment friendly bio-sorbent for protecting health of the poor from ill effects of arsenic. In the present investigation, we prepared bio-sorbent from the solid waste seed biomass of Mangifera indica (M), Artocarpus heterophyllus (JF), and Schizizium commune (JP). The characterization of bio-sorbents has been done by using different techniques namely FTIR and XRD. Arsenic concentration was estimated using ICP and adsorption parameters optimized for pH, adsorbent dose, and initial arsenic concentration. At pH 8.4, kinetics study of arsenic removal was M (94%), JF (93%), and JP (92%) for initial concentration of 2.5 ppm. The adsorption kinetics was well explained by Freundlich model and pseudo-second reaction order.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: Arsenic removal; Bio-adsorbent; Biochar; Mangiferaindica; Schiziziumcommun; Arsenic; Chemicals removal (water treatment); Developing countries